Controlled Directional Water‐Droplet Spreading on a High‐Adhesion Surface1. Issue 24 (12th May 2014) - Feng, Shile; Wang, Sijie; Gao, Longcheng; Li, Guangjun; Hou, Yongping; Zheng, Yongmei
Abstract Controlled directional spreading of a droplet on a smart high‐adhesion surface was made possible by simply controlling anodic oxidation. The wettability gradient of the surface was controlled from 0.14 to 3.38° mm−1 by adjusting the anodic oxidation conditions. When a water droplet made contact with the substrate, the droplet immediately spread in the direction of the wettability gradient but did not move in other directions, such as those perpendicular to the gradient direction, even when the surface was turned upside down. The spreading behavior was mainly controlled by the wettability gradient. Surfaces with a V‐ or inverse‐V‐shaped wettability gradient were also formed by the same method, and two droplets on these surfaces spread either toward or away from one another as designed. This method could be used to oxidize many conductive substrates (e.g., copper, aluminum) to form surfaces with variously shaped wettability gradients. It has potential for application in microfluidic devices.